Pembagian Harta Warisan Kepada Anak di Luar Nikah Menurut Hukum Islam Dan Hukum Perdata - Fernanda Nur Latifah (Fakultas Hukum Universitas Janabadra, 2021)
Inheritance is an asset left by a person to their heirs. When that person dies, the inheritance must be divided according to Islamic law and civil law in Indonesia. Islamic law is law that originates and becomes part of the Islamic religion. The conception of Islamic law, its basis, and legal framework are established by Allah. In Islamic law also regulates inheritance. The definition of Islamic inheritance law is a rule designed to regulate the case or ownership of a person who died globally to a person or family who is also claimed to be an heir. The distribution of inheritance is prioritized for those who have blood with heirs according to article 832 of the Civil Code and in the Quran An-Nisa paragraph 7. The problem is if the child is born out of wedlock and the division of inheritance between civil law and Islamic law because there are differences in the principles that must be used. This paper mainly discussing two question; How is inheritance divided according to Islamic law and civil law? And how is inheritance distributed to children out of wedlock? This research is a doctrinal research with statute as well as comparison approach. The paper concludes that the children out of wedlock who have been recognized by their fathers according to the Civil Code article 863 get 1/3 part because children outside of marriage who have been recognized by their fathers are included in the first group, meanwhile according to Article 210 of KHI (1), a person who is at least 21 years of age and has common sense without coercion can donate a maximum of 1/3 (one third) of his or her property to another person or institution in front of two witnesses.